(untitled) (Medical Forum Monthly, 2024)
Objective: To assess health-related quality of life and co-morbidity pattern in hemodialysis patients Study Design: Observational / cross sectional study. Place and Duration of Study: This study was carried out in the Department of Nephrology Department, Nishtar Medical Hospital, Multan from February 2015 to January 2016. Materials and Methods: By a non probability purposive sampling procedure, 123 hemodialysis patients from our hemodialysis center in Nishtar Hospital Multan(Pakistan) were interviewed by resident doctor according to the SF-36 Scales. The means and standard deviations for each of eight scales were calculated, each domain ranges from 0-100, the highest scores indicating better quality of life. Comorbidities like DM, Hypertension ,ischemic heart disease lung disease etc were also recorded. Results: The scores of the eight scales in the hemodialysis patients were 49.92 ±30.90, 38.82 ±41.39, 46.73 ±26.54, 40.52 ± 21.65, 43.98 ±21.82, 49.43 ±27.76, 49.85 ±40.59 and 59.93 ±17.36. Co-morbidities pattern were hypertension in 104(84.6%),DM 59(48%),ischemic heart disease 23(18.7%) and other co morbidities were less common. The scores of most of the scale in the patients with co morbidities were lower as compared to patients without co morbidities. Data obtained was entered by a doctor in SPSS version 20 and was analyzed to compute descriptive statistics of the numerical variables while frequencies and their percentages for categorical variables of the study. Conclusion: The results of our study indicate that quality of life was poor among patients on hemodialysis particularly those having co-morbidities. Hypertension and diabetes were major co-morbidities in our study. Quality of life score was lower in female patients than that of male patients. Proper management of co-morbidities can improve quality of life of these patients which will decrease disease morbidity and mortality. This will also provide psychological and financial relief to the suffering families and also be cost effective for hospital authorities in terms of availability of space.